Răspuns :
a=√(5+3√3)²
a=|5+3√3|
a=5+3√3
b=|5-3√3|
b=3√3-5
ma=a+b/2
ma=5+3√3+3√3-5/2
ma=6√3/2
ma=3√3
mg=√a×b
mg=√(5+3√3)(3√3-5)
mg=√(3√3+5)(3√3-5)
mg=√(3√3)²-5²
mg=√27-25
mg=√2
[tex]\it a = \sqrt{(5 + 3\sqrt{3})^{2} } <=> a = |5 + 3\sqrt{3}| <=> a = 5 + 3\sqrt{3} \\ \\ b = |5 - 3\sqrt{3}| = -(5 - 3\sqrt{3}) = -5 + 3\sqrt{3} \\ \\ m_{a} = \frac{a~+~b}{2} = \frac{5 + 3\sqrt{3} - 5 + 3\sqrt{3} }{2} = \frac{6\sqrt{3} }{2} = 3\sqrt{3} \\ \\ m_{g} = \sqrt{a \cdot b} = \sqrt{(5 + 3\sqrt{3})(-5 + 3\sqrt{3})} = \sqrt{(3\sqrt{3} + 5)(3\sqrt{3} - 5) } = \sqrt{(3\sqrt{3})^{2} - 5^{2} } = \\ = \sqrt{27 - 25} = \sqrt{2}[/tex]